The metabolic profile of mitoxantrone and its relation with mitoxantrone-induced cardiotoxicity - Rossato, Luciana Grazziotin (2013)
Mitoxantrone (MTX) is an antitumor agent that causes cardiotoxicity in 18 % patients. The metabolic profile of MTX was assessed after incubation of 100 lM MTX with hepatic S9 fraction isolated from rats. The presence of MTX and its metabolites was also assessed in vivo through the analysis of liver and heart extracts of MTX-treated rats. The cytotoxic effects of MTX and MTX metabolites were evaluated in the H9c2 cells after 24-h incubation with MTX alone and MTX ? metabolites. The influence of CYP450- and CYP2E1-mediated metabolism for the cytotoxicity of MTX was assessed after 96-h incubation with MTX (100 nM and 1 lM) in the presence/ absence of CYP450 or CYP2E1 inhibitors. After 4-h incubation in supplemented S9 fraction, the MTX content was 35 % lower and 5 metabolites were identified: an acetoxy ester derivative (never described before), two glutathione conjugates, a monocarboxylic acid derivative, and the naphtoquinoxaline, the later commonly related to MTX pharmacological effects. The presence of MTX and naphtoquinoxaline metabolite was evidenced in vivo in liver and heart of MTX-treated rats. The cytotoxicity caused by MTX ? metabolites was higher than that observed in the H9c2 cells incubated with non-metabolized MTX group. The co-incubation of MTX with CYP450 and CYP2E1 inhibitors partially prevented the cytotoxicity observed in the MTX groups incubated with H9c2 cells, highlighting that the metabolism of MTX is relevant for its undesirable effects. The naphtoquinoxaline metabolite is described in heart and liver in vivo, highlighting that this metabolite accumulates in these tissues. It was demonstrated that MTX P450-mediated metabolism contributed to MTX toxicity.